2013
DOI: 10.1037/a0030027
|View full text |Cite
|
Sign up to set email alerts
|

Context-dependent control over attentional capture.

Abstract: A number of studies have demonstrated that the likelihood of a salient item capturing attention is dependent on the “attentional set” an individual employs in a given situation. The instantiation of an attentional set is often viewed as a strategic, voluntary process, relying on working memory systems that represent immediate task priorities. However, influential theories of attention and automaticity propose that goal-directed control can operate more or less automatically on the basis of longer-term task rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
103
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(116 citation statements)
references
References 87 publications
(219 reference statements)
11
103
2
Order By: Relevance
“…However, it has also been proposed that goal-directed control can operate more or less automatically on the basis of learned task representations, suggesting a complementary control mechanism that might attenuate distraction without relying on limited-capacity executive processes such as working memory (Norman & Shallice, 1986; Schenider & Shiffrin, 1977; Logan, 1988). Consistent with such a view, recent studies have demonstrated that past experience plays a critical role in determining distraction (e.g., Leber & Egeth, 2006; Vatterott & Vecera, 2012), and it has been shown that these effects reflect relational learning processes that tie information regarding particular attentional states to their learned context (Cosman & Vecera, 2012; Leber, Kawahara, & Gabari, 2009). …”
mentioning
confidence: 76%
See 1 more Smart Citation
“…However, it has also been proposed that goal-directed control can operate more or less automatically on the basis of learned task representations, suggesting a complementary control mechanism that might attenuate distraction without relying on limited-capacity executive processes such as working memory (Norman & Shallice, 1986; Schenider & Shiffrin, 1977; Logan, 1988). Consistent with such a view, recent studies have demonstrated that past experience plays a critical role in determining distraction (e.g., Leber & Egeth, 2006; Vatterott & Vecera, 2012), and it has been shown that these effects reflect relational learning processes that tie information regarding particular attentional states to their learned context (Cosman & Vecera, 2012; Leber, Kawahara, & Gabari, 2009). …”
mentioning
confidence: 76%
“…Critically, when neurologically healthy participants train briefly on the heterogeneous search task prior to the homogeneous search task, as in the current design, distractor effects in homogeneous displays are similarly attenuated (Leber & Egeth, 2006). These effects of learning on attentional control appear to be long-term, persisting across delays of up to a week (Leber et al, 2009), and are strongly context-dependent (Cosman & Vecera, 2012). Of primary interest in the current work was whether, relative to healthy comparisons, amnesic patients would show an impaired ability to use past experience to overcome attentional capture following a brief (∼5 minute) delay between heterogeneous training and homogeneous testing sessions.…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with Bacon and Egeth (1994), Leber and Egeth (2006a) confirmed that singleton detection training lead to a significantly larger distractor cost -i.e., more slowing of reaction time in the presence of a color singleton -compared to feature search training, in a post-test session wherein all participants were exposed to the standard additional singleton paradigm (see also Leber & Egeth, 2006b, Leber, Kawahara, & Gabari, 2009Cosman & Vecera, 2013 for similar results). Thus, manipulating search strategy through brief attentional training induced the predicted behavioral effects with respect to distractor processing.…”
Section: Accepted Manuscriptmentioning
confidence: 89%
“…In the test phase it was found that the search mode employed in ambiguous blocks (wherein either mode could be used) was determined by the irrelevant background on which the trails were presented (Cosman and Vecera 2013). This suggests that automatic responses to a task may depend on long-term memory representations (Carlisle et al, 2011) that are cued by the initial context in which a task takes place.…”
Section: Discussionmentioning
confidence: 99%